2002
DOI: 10.1590/s0100-879x2002000300001
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy and cardioprotection: mechanisms and controversies

Abstract: Epidemiological and case-controlled studies suggest that estrogen replacement therapy might be beneficial in terms of primary prevention of coronary heart disease (CHD). This beneficial effect of estrogens was initially considered to be due to the reduction of low density lipoproteins (LDL) and to increases in high density lipoproteins (HDL). Recent studies have shown that estrogens protect against oxidative stress and decrease LDL oxidation. Estrogens have direct effects on the arterial tissue and modulate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
2
18
0
1
Order By: Relevance
“…On the other hand, HDL declined with age in males but actually increased in females. These results support the role of estrogen in modulating HDL, a mechanism thought to explain, in part, the protection against cardiovascular disease in premenopausal women (26 ).…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, HDL declined with age in males but actually increased in females. These results support the role of estrogen in modulating HDL, a mechanism thought to explain, in part, the protection against cardiovascular disease in premenopausal women (26 ).…”
Section: Discussionsupporting
confidence: 76%
“…7 More recently, studies have also demonstrated an antioxidant effect by estrogen, reducing LDL oxidation in vivo and in vitro. 43 The direct effects of estrogen on the vascular system and which modulate the vascular tonus comprise 1) acute vasodilatation, increasing the synthesis and bioactivity of nitric oxide; 44,45 2) long-term modulation of vascular tonus, regulating the production of prostaglandins and expression of eNOS and the endothelin gene 46 ; 3) inhibition of endothelin-induced vasoconstriction 47 ; and 4) inhibition of sympathetic activity. 27 In addition to these actions on the vascular tonus, estrogen exerts an antiproliferative action on the vascular smooth layer.…”
Section: Estrogen Menopause and Endothelial Functionmentioning
confidence: 99%
“…1 Genistein, a phytoestrogen, binds to estrogen receptors, thereby exerting estrogenic effects, and has therefore been proposed as a natural alternative to estrogen replacement. 2 Evidence suggests that genistein exhibits a potency similar to that of 17b-estradiol (each administered at 100 mg=kg i.v.)…”
Section: Introduction Lmentioning
confidence: 99%